Abdominal Pseudocyst: A Rare Complication of Ventriculoperitoneal Shunting - Faisal; Dharmajaya, Ridha; Tala, Muhammad Ihsan Zulkarnain; Mousa, Abdurrahman; Tandean, Steven (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2019)
Abstract: Ventriculoperitoneal (VP) shunt placement is one of the most commonly performed procedures in neurosurgery. One rare complication is the formation of an abdominal pseudocyst, which can cause shunt malfunction.